Functional state of back muscles in patients with degenerative spine disorders - Skidanov, Artem; Dupliy, Diana; Kotulskiy, Igor; Barkov, Oleksandr; Kis, Andrey; Piontkovsky, Valentyn; Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Structural changes in the cases of degenerative spine disorders are considered to be related to the processes that develop in vertebral movement segments and paravertebral ligaments and muscles. Goal: to investigate functional state of paravertebral muscles in patients with degenerative disorders of lumbar spine (LS) before and after surgical treatment. Methods: electromyography of 117 patients with degenerative disorders of LS and 10 healthy volunteers was performed. Patients were divided on groups according to their diagnosis: hernia of intervertebral discs of LS, instability, spondylolisthesis and stenosis. Interferential myography of m. erector spinae on the level of LIV–LV vertebras in state of longtime (60 s) strain was recorded and spectral characteristics were calculated — general power of spectrum (GPS) medium power of spectrum (MPS), medium frequency (MF), median of spectrum frequency (MSF), speed of frequency change (SFC). The investigations were analysed before surgical intervetion and 6, 18 and 36 months after it. Results: significantly lower indices GPS and MF were revealed before operation in patients with spondylolisthesis and even lower – in patients with stenosis in comparison with control. The indices GPS, MPS and MSF decreased in all patients’ groups after operation, but more significantly in patients with spondylolisthesis. Dynamics of spectrum indices was performed, it revealed decrease of GPS, MPS and MSF during 18 months, but from 18 months to 3 year and later these indices have been restored up to preoperative levels. Conclusions: on the background of degenerative disorders of LS the functional capabilities of paravertebral muscles decreased in all patients, to the maximum in patients with spondylolisthesis and stenosis. The more significant differences in GPS, MPS and MSF were revealed in group of patients with spondylolisthesis in comparison with control. As opposed to complete clinical restoration (in 1 year) an electrophysiological restoration of m. erector spinae was noticed in 3 year after surgical treatment.